A Persian Intellectual in the 19th Century Ottoman Capital: Mirza Habib Isfahani and His Tereke - (:unkn) unknown (ISAM, 2017)
There exists a relatively extensive literature relating to the biography and the intellectual and political identity of the nineteenth century intellectual adversary Mirza Habib Isfahani, who spent half of his life in the Istanbul in exile, where soon after his arrival he became a celebrated figure in intellectual circles. His acclaim was a consequence of his literary scholarship as the author of a number of Persian works on grammar; his authorship of Hatt ve Hattatan; his translation of Serguzest-i Haci Baba-yi Isfehani; and his contributions to the newspaper Akhtar, the first and longestrunning Persian newspaper published in the Ottoman capital. This literary scholar was also a civil servant of the Ottoman state. By focusing on Mirza Habib Isfahani's tereke (the bequest of possessions) this articles will attempt to shed light on his biography and intellectual world. Moreover, owing to the fact that a significant part of this possessions consisted of books and manuscripts left behind by this important nineteenth-century figure, this examination will provide information pertaining to the literary legacy of Ottoman and Iranian intellectuals of the period.
Keywords: Mirza Habib Isfahani; Istanbul; Persian; Iranian Intellectual; Persian language and Literature; Booklist